(untitled) (Latakia University Journal -Basic Sciences Series, 2024)
A series of new fluorine derivative have been synthesized. The compound (1) was prepared by esterification of 9H-fluorene-2-carboxylic acid with concentrated sulphuric acid in absolute ethanol. The compound (2) was prepared by treatment fluorine etanawate with hydrate hydrazine in absolute ethanol. compound (2) with carbon disulphide in alkaline medium afforded after acidic treatment the compound (3). The compound (4) was prepared by condensation of compound (2) with 2-chloroacetamide.The compound (5) was prepared by treatment of compound (2) with phenylisothiocyanate. The compound (5) was oxidatively cyclised to the compound (6) by elimination of H2S using iodine and potassium iodide in ethanolic sodium hydroxide. The compound (7) was obtained by cyclisation of the compound (5) by treating with cold concentrated sulphuric acid. The compound (5) by heating with 4N(NaOH) through dehydration to afford the compound (8). The structures of synthesized compounds has been established on the basis of their spectral (FT-IR, 1H-NMR, 13C-NMR, elemental analysis) data. TLC confirmed the purity of the compounds.